2007
DOI: 10.1002/smj.635
|View full text |Cite
|
Sign up to set email alerts
|

Risk sharing in supplier relations: an agency model for the Italian air‐conditioning industry

Abstract: This study of risk sharing in the Italian high precision air conditioning (AC) industry confirms agency theory predictions that buyers absorb risk to a non‐negligible degree, and that they absorb more risk (a) the greater the supplier's environmental uncertainty, (b) the more risk averse the supplier, and (c) the less severe the supplier's moral hazard. The analyzed buyers accommodate for unforeseen and uncontracted‐for cost fluctuations, which is consistent with relational contract theory. The study clarifies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…The studies on "lean suppliers" by the International Motor Vehicle Program at MIT (Cusumano & Takeishi, 1991;Helper & Sako, 1995, 1998Helper & MacDuffie, 1997;Fine, 1998) showed that North American and European assemblers and suppliers were converging towards Japanese-style supplier relation management, moving from competitive, adversarial relationships, to more cooperative ones, characterized by risk-sharing practices (Camuffo, Furlan, & Rettore, 2007). More recently, Helper, MacDuffie and Sabel (2000) suggest that "voice" practices like benchmarking, co-design, and "root cause" error detection and correction are the pragmatist mechanisms that constitute "learning by monitoring" a relationship in which buyers and suppliers continuously improve their joint products and processes and therefore their capabilities.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…The studies on "lean suppliers" by the International Motor Vehicle Program at MIT (Cusumano & Takeishi, 1991;Helper & Sako, 1995, 1998Helper & MacDuffie, 1997;Fine, 1998) showed that North American and European assemblers and suppliers were converging towards Japanese-style supplier relation management, moving from competitive, adversarial relationships, to more cooperative ones, characterized by risk-sharing practices (Camuffo, Furlan, & Rettore, 2007). More recently, Helper, MacDuffie and Sabel (2000) suggest that "voice" practices like benchmarking, co-design, and "root cause" error detection and correction are the pragmatist mechanisms that constitute "learning by monitoring" a relationship in which buyers and suppliers continuously improve their joint products and processes and therefore their capabilities.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…According to Camuffo et al (2007), task programmability can help to reduce the information asymmetry.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…0.770 (Camuffo et al, 2007;Mentzer et al, 2001) RIS2 When there are any problems in the supply materials (or product), our company and suppliers will cooperate with each other to share the related costs.…”
Section: 615mentioning
confidence: 99%
See 2 more Smart Citations